Blueprint - Bhatia, Gautam, 1952- (2018)
How does one view the cumulative work of one's life? For Gautam Bhatia, this publication is not merely a record of his personal or professional legacy, but rather it is a profound examination of his life in architecture. According to the author, architecture is, by its very nature, a practice of contradictions. It operates under influences from sociology, design, engineering, landscape, anthropology, urbanism and civic practice in order to impose its will on the nature of space. This publication brings together several of the author's built works, from commercial and residential buildings to large public spaces, from places of leisure to places of worship. Together with detailed essays, drawings and photographs, the author lays out his philosophy of design to illustrate how architecture became not just a conquest of the imagination, but also of reality.
Keywords: Bhatia, Gautam, -- 1952-; Architects -- India; Architecture -- India; Blueprints -- India; Architects; Architecture; Blueprints; India